2015
DOI: 10.1039/c5cc01307k
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrolled synthesis of vicinally functionalized piperidines by nucleophilic β-addition of alkyllithiums to α-aryl substituted piperidine enecarbamates

Abstract: Substituted piperidines are emerging as important medicinally-active structural motifs. Here, we report highly stereoselective carbolithiation reactions of α-aryl piperidine enecarbamates that offer direct access to vicinally-substituted piperidine compounds. We have also demonstrated that the carbanion intermediates can be trapped with a carbon electrophile

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Of note, the deprotonating base, temperature, and reaction time are key adjustable parameters for mitigating deformylation (where applicable), α′-, allylic-, aryl-, or reductive-lithiation. As noted earlier, in our previous vicinal difunctionalization strategy, 67 we were not able to achieve β-arylation nor α-alkylation of dehydropiperidines. 9 The importance of the α-selenonyl group in this reaction manifold is highlighted by the observation that α-carbo-functionalized enecarbamates such as 2a/b/d (see Scheme 2) fail to react under the specified conditions.…”
Section: Functionalized Piperidines and Azepanes (Examples Of Which Amentioning
confidence: 57%
“…Of note, the deprotonating base, temperature, and reaction time are key adjustable parameters for mitigating deformylation (where applicable), α′-, allylic-, aryl-, or reductive-lithiation. As noted earlier, in our previous vicinal difunctionalization strategy, 67 we were not able to achieve β-arylation nor α-alkylation of dehydropiperidines. 9 The importance of the α-selenonyl group in this reaction manifold is highlighted by the observation that α-carbo-functionalized enecarbamates such as 2a/b/d (see Scheme 2) fail to react under the specified conditions.…”
Section: Functionalized Piperidines and Azepanes (Examples Of Which Amentioning
confidence: 57%
“…The rst example of highly diastereoselective carbolithiations, followed by protonation, of a-arylated dehydro-piperidine enecarbamates 120 with alkyllithium nucleophiles was also described (Scheme 41). 57 This umpolung-type synthetic sequence can lead to the diastereoselective synthesis of piperidine derivatives bearing vicinal (C2, C3) substituents, providing a method to obtain difunctionalized piperidines, useful precursors for the synthesis of compounds of medicinal and biological importance. The carbolithiation process is highly diastereoselective, with the C-2 aryl and the C-3 alkyl groups in anti position.…”
Section: Aryl Vinyl Carbamatesmentioning
confidence: 99%
“…2B). 33 In that report, it was noted that incipient attempts at methylating the benzylic organolithium generated from enecarbamate 3a were quite promising (see 5a, Fig. 2C).…”
mentioning
confidence: 94%
“…32 Additionally, we and Sarpong have revealed that the addition of organolithium nucleophiles to the β-position of α-arylated piperidine enecarbamates such as 3 followed by protonation of the resulting intermediate tertiary organolithium, is possible, under additive-free conditions (see 4, Fig. 33 In that report, it was noted that incipient attempts at methylating the benzylic organolithium generated from enecarbamate 3a were quite promising (see 5a, Fig. 33 In that report, it was noted that incipient attempts at methylating the benzylic organolithium generated from enecarbamate 3a were quite promising (see 5a, Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation